2017
DOI: 10.1016/j.jval.2016.09.2397
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Data for the Evaluation of Transarterial Radioembolization versus Sorafenib in Hepatocellular Carcinoma: A Cost-Effectiveness Analysis

Abstract: From an Italian health care service perspective, TARE could be a cost-effective strategy in comparison with sorafenib for patients with intermediate or advanced HCC. The results from forthcoming randomized controlled trials comparing TARE with sorafenib will be able to confirm or reject the validity of this preliminary evaluation. In the meantime, decision makers can use these results to control and coordinate the diffusion of the technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 46 publications
1
69
0
Order By: Relevance
“…For advanced stage patients, the incremental cost-effectiveness ratio of TARE versus TACE resulted 360$ per month (3120$ per year). A more recent study performed in Italy [ 13 ] reported for intermediate stage patients an incremental cost-utility ratio (ICUR) for TARE vs. sorafenib of 3302€/QALY, whilst for advanced stage patients, TARE seemed to be a dominant strategy (lower costs and greater health improvements) compared to sorafenib.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For advanced stage patients, the incremental cost-effectiveness ratio of TARE versus TACE resulted 360$ per month (3120$ per year). A more recent study performed in Italy [ 13 ] reported for intermediate stage patients an incremental cost-utility ratio (ICUR) for TARE vs. sorafenib of 3302€/QALY, whilst for advanced stage patients, TARE seemed to be a dominant strategy (lower costs and greater health improvements) compared to sorafenib.…”
Section: Introductionmentioning
confidence: 99%
“…The cost-effectiveness model developed by Rognoni et al [ 13 ] has been applied to perform a BIA considering increasing utilization rates of TARE in place of sorafenib for the treatment of intermediate-advanced stage HCC patients in the Italian healthcare system over a 5-years horizon.…”
Section: Introductionmentioning
confidence: 99%
“…Patients started progression‐free status, then moved to progression disease or death (Figure ). This type of model has been used frequently to evaluate the cost‐effectiveness of therapies for advanced liver cancer . The model used a 1‐month cycle length extending over a 10‐year time horizon.…”
Section: Methodsmentioning
confidence: 99%
“…The methods either consider known confounders only, or also unknown confounders through the use of instrumental variables in the multivariate regression (Prentice JC et al 2014). Examples of the use of observational data to assess the cost-effectiveness of MDs include the study by Armeni et al (2016) on MitraClip for patients with moderate/severe mitral regurgitation and by Rognoni et al (2016) on transarterial radioembolization for patients with hepatocellular carcinoma. Both of these studies used the propensity scoring method.…”
Section: Improving the Analysis Of The Available Clinical Datamentioning
confidence: 99%